Caracterización del extracto acuoso de tzinzo (Tagetes minuta) en función de la composición química y capacidad antioxidante” - Morales Chicaiza, Ginger Solange (2023)
The present investigation take as objective to characterize the aqueous extract of Tzinzo (Tagetes minuta) in terms of its chemical composition and antioxidant capacity. The collection and selection of raw material were carried out, followed by cutting the leaves under optimal conditions. The leaves were subjected to a drying process to obtain the raw drug. Through the application of phytochemical profiling methodology, secondary metabolites were identified in the aqueous extract, including alkaloids, phenolic compounds, flavonoids, mucilages, and bitter principles. An experimental design using response surface methodology was implemented for extraction, using the statistical software Design Expert 8.0.6. The optimal conditions were ethanol concentration of 87,34 % w/w, extraction time of 12 h, and temperature of 69,39 °C, this generated a polyphenol content of 268,76 mg/g and an antioxidant capacity of 870.16 (μmol Fe2+/g sample). Physicochemical analyses of the optimized extract revealed a pH of 5, 22; acidity of 0, 31 % w/w sulfuric acid, and moisture content of 95, 01 % w/w. The reducing antioxidant capacity of iron was 0,756 (μM Fe2+/g sample). Using gas chromatography with mass detector, the chemical composition of the aqueous extract of Tzinzo was determined, identifying 9 volatile compounds. The main components were trans-tagetone (36, 44 %), trans anethole (15, 50 %), and phytol (19, 49 %). Regarding antioxidant effectiveness expressed in IC50, the results for the ABTS method showed a concentration of 0, 34 (0, 02) mg/ml, and for the FRAP method, a concentration of 765, 20 (6, 45) (μmol Fe2+/g sample) was obtained. These results indicate the presence of antioxidants capable of neutralizing free radicals. The study concluded that the aqueous extract of Tagetes minuta possesses significant antioxidant capacity due to its chemical composition of phenolic compounds, flavonoids, and volatiles. These findings suggest that the extract could have potential applications in the food and pharmaceutical industries as a natural antioxidant agent.